Fecal Incontinence: Prevalence, Severity, and Quality of Life Data from an Outpatient Gastroenterology Practice - Eva H. Alsheik; Thomas Coyne; Sara K. Hawes; Laleh Merikhi; Scott P. Naples; Nandhakumar Kanagarajan; James C. Reynolds; Scott E. Myers; Asyia S. Ahmad (Gastroenterology Research and Practice)
Background. The prevalence of fecal incontinence varies tremendously as a result of inadequate data collection methods. Few office-based studies have assessed the prevalence of fecal incontinence and none have looked at modifiable risk factors or effect on quality of life. Design, Settings, Patients, and Main Outcome Measures. Five hundred patients who visited our inner city, university-based gastroenterology practice, were asked about symptoms of fecal incontinence. We also retrospectively reviewed 500 charts to identify the frequency of patient-physician reporting of fecal incontinence. Results. Of the 500 patients that were directly questioned, 58 (12%, 43 women, 15 men) admitted to fecal incontinence compared to 12 (2.4%) in the retrospective arm. Patients with fecal incontinence and loose/watery stool reported the lowest quality of life scores. While the average severity score was similar between men and women, women had a significantly lower average quality of life score (3.04 versus 2.51; P<0.03). Conclusions. The identification of fecal incontinence increases when patients are directly questioned. Identifying and treating patients with loose stool is a potential strategy to improve quality of life in this patient population. In men and women with similar severity of fecal incontinence, women have a significantly lower quality of life.